2017
DOI: 10.1016/j.clml.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk of Cardiac Events in Patients With Previously Treated Multiple Myeloma Versus Matched Patients Without Multiple Myeloma: An Observational, Retrospective, Cohort Study

Abstract: The present study provides the first known comparison of cardiac event risk in patients with MM versus age- and gender-matched patients without MM. The cardiac event risk was greater in MM patients with ≥ 3 previous drugs for any cardiac event, dysrhythmias, congestive heart failure, cardiomyopathy, and conduction disorders compared with patients without MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 51 publications
(64 reference statements)
0
38
0
3
Order By: Relevance
“…Антрациклин-индуцированная кардиотоксичность носит кумулятив-ный, дозозависимый характер и приводит к необра-тимому повреждению сердца. Например, кумулятив-ная доза доксорубицина 400 мг/м 2 в 5% случаев со-пряжена с развитием застойной СН, а при назначении высоких доз доксорубицина (700 и более мг/м 2 ) про-исходит экспоненциальное, до 48%, увеличение рис-ка развития хронической сердечной недостаточности (ХСН) [4][5][6][7]. Однако существуют значительные разли-…”
Section: Ivabradin In Prevention Of Anthracycline Cardiotoxicity ивабunclassified
“…Антрациклин-индуцированная кардиотоксичность носит кумулятив-ный, дозозависимый характер и приводит к необра-тимому повреждению сердца. Например, кумулятив-ная доза доксорубицина 400 мг/м 2 в 5% случаев со-пряжена с развитием застойной СН, а при назначении высоких доз доксорубицина (700 и более мг/м 2 ) про-исходит экспоненциальное, до 48%, увеличение рис-ка развития хронической сердечной недостаточности (ХСН) [4][5][6][7]. Однако существуют значительные разли-…”
Section: Ivabradin In Prevention Of Anthracycline Cardiotoxicity ивабunclassified
“…7 Of interest, the incidence of cardiovascular disease has been described to be higher in patients with MM (60.1%) than in non-MM patients (54.5%) 7 and a recent review and meta-analysis of patients enrolled in clinical trials with carfilzomib showed that the incidence of all grade and grades ≥3 cardiovascular adverse events (CVAEs) was 18.1% and 8.2%, respectively. 8 Although carfilzomib is one of the most cardiotoxic and, at the same time, effective novel agents used in MM treatment, it is not the only anti-myeloma drug characterized by a high risk of CVAEs.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a challenging disease to manage with a number of age-and disease-related comorbidities [1][2][3][4]. While renal and bone disease are among the most common comorbidities, patients with MM are also at a higher risk for developing cardiovascular comorbidities due to the interaction of patient-related (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While renal and bone disease are among the most common comorbidities, patients with MM are also at a higher risk for developing cardiovascular comorbidities due to the interaction of patient-related (e.g. diabetes, diet, lipid levels, weight), disease-related, and treatment-related risk factors [4]. An observational retrospective cohort study (2006)(2007)(2008)(2009)(2010)(2011) reported a significantly higher prevalence of cardiovascular events in previously treated patients with MM versus those without MM (52% vs 35% p < 0.0001), including elevated rates of arrhythmias, congestive heart failure, cardiomyopathies, and conduction disorders [4].…”
Section: Introductionmentioning
confidence: 99%